Mothers’perceptions and exposure to information associated with the acceptance of children’s tuberculosis prevention therapy in Bali Indonesia - I Made Arta; Sawitri, Anak Agung Sagung; Ni Ketut Sutiari (Universitas Udayana, 2023)
Background and purpose: Children face risk of tuberculosis (TB) infection within households where an index case is present. TB prevention therapy (TPT) for children is a recommended measures to provide protection against TB. This study aims to investigate the relationship between maternal perceptions and the information exposure received by mothers with the acceptance of TPT for toddlers. Methods: A cross-sectional study was conducted in Badung District, Bali Province, using the register of tuberculosis patients from 2018-2019 as the sampling frame. A systematic random selection yielded 138 mothers with eligible criteria out of 226 children. Home interviews was conducted with mothers regarding maternal characteristics, knowledge, toddlers’ characteristics, perceptions, information exposure, and acceptance of TPT for their children. The relationship between acceptance of TPT and perceptions, information, and other variables was tested using Chi-square test, followed by multivariable analysis using forward logistic regression. Results: The majority of mothers were aged 30-39 years (57.8%), had completed high school (43.5%), unemployed (43.5%), resided in the Kuta sub-district (23.9%), and had ≤2 living children (73.2%). About 19.2% of mothers accepted TPT for their children. The acceptance of TPT for children was significantly associated with information sources from health worker (aOR=26.70; 95%CI: 1.25-569.38), the presence of ≥2 family members with TB (aOR=14.29; 95%CI: 1.22-166.68), duration of child care by the index case ≥8 hours/day (aOR=10.04; 95%CI: 2.05-49.26), receiving complete information (aOR=9.01; 95%CI: 1.64-49.64), and perceiving minimal barriers (aOR=4.08: 95%CI: 1.22-13.62). Conclusion: Adequate information exposure, longer duration of care by TB patients, and low perceived barriers contribute to the acceptance of TPT for children. Education to parent is essential to improve acceptance to TPT.